Using the concept of management information system to improve an effusive intelligent parking system - Yass, A.A.; Yasin, N.M. (2009)
MIS is interchangeably known as management information system or management information service. MIS refers broadly to a computer-based system that provides users with the tools for organizing, evaluating and efficiently running their organizations. In this paper we review the techniques used in parking systems. In particular we describe how the principles of MIS are used to improve the system used in car park environment; thus proposing a new design for intelligent parking system to overcome the current parking problems. This paper focuses on the Malaysian parking system as the research case study and also discus of involving the sensor and having an efficient design overcome the current problems at the parking system at Malaysia